New product, old problem(s): multistate outbreak of Salmonella Paratyphi B variant L(+) tartrate(+) infections linked to raw sprouted nut butters, October 2015. (8th October 2018) - Heiman Marshall, K. E.; Booth, H.; Harrang, J.; Lamba, K.; Folley, A.; Ching-Lee, M.; Hannapel, E.; Greene, V.; Classon, A.; Whitlock, L.; Shade, L.; Viazis, S.; et al.
Abstract: A cluster of Salmonella Paratyphi B variant L(+) tartrate(+) infections with indistinguishable pulsed-field gel electrophoresis patterns was detected in October 2015. Interviews initially identified nut butters, kale, kombucha, chia seeds and nutrition bars as common exposures. Epidemiologic, environmental and traceback investigations were conducted. Thirteen ill people infected with the outbreak strain were identified in 10 states with illness onset during 18 July–22 November 2015. Eight of 10 (80%) ill people reported eating Brand A raw sprouted nut butters. Brand A conducted a voluntary recall. Raw sprouted nut butters are a novel outbreak vehicle, though contaminated raw nuts, nut butters and sprouted seeds have all caused outbreaks previously. Firms producing raw sprouted products, including nut butters, should consider a kill step to reduce the risk of contamination. People at greater risk for foodborne illness may wish to consider avoiding raw products containing raw sprouted ingredients.